(untitled) (Global Journals of Research in Engineering, 2023)
Concrete structures can be strengthened by using repair restoration and development Fiber-reinforced polymers where the use these materials has increased in recent years because of the many advantages of these compounds compared to traditional materials such as steel Among the most important of these features are a high strength-to-weight ratio high energy absorption and resistance excellent abrasion and high tensile strength By taking the following two variables 1- The number of layers of carbon fiber 2- Rotate the edges of the samples The analytical results showed good agreement with the experimental results and the analytical model showed the importance of the fibers Rounded cross-section edges and the number of carbon fiber layers increase the bearing capacity of the concrete columns also rounding the edges of the column prevented the concentration of stresses and contributed to the increase of the enclosing area